DEVELOPMENT OF GEL DOSAGE FORM OF ETHYL ACETATE EXTRACT OF MANGOSTEEN RIND - Ketut Widyani Astuti; Ni Putu Ayu Dewi Wijayanti; I Gusti Ngurah Jemmy Anton Prasetia (Institute for Research and Community Services Udayana University, 2017)
Abstract Alpha-mangostin is a xanthonoid compound contained in mangosteen rind (Garcinia mangostana L.) and has an antibacterial effect against Staphylococcus aureus, the bacterium that causes acne. In this study, mangosteen rind extract is formulated in a gel dosage form. This study aimed to determine the optimum formula, the physical and chemical properties as well as the optimum formula release profile of the gel dosage form of mangosteen rind extract. The mangosteen rind extract gel formula consists of viscolam, propylene glycol, glycerin, microcare®, ethyl acetate extract of mangosteen rind, and distilled water. The formula was optimized by varying the concentrations of viscolam (2% and 5%), propylene glycol (5% and 20%) and glycerin (2% and 15%) using a factorial experimental design program called Design Expert 7.0.0. The 8 formulas were developed into gel dosage form and the physical and chemical properties were then evaluated. The evaluation tests include viscosity, dispersive power, and pH tests. The evaluation results were processed using the Design Expert 7.0.0 program to determine the optimum formula. The results of the analysis showed the optimum formula of gel dosage form of mangosteen rind extract with viscolam percentage of 4.97%, propylene glycol of 9.91%, glycerin of 12.23%, microcare® of 0.3%, TEA (q.s), ethyl acetate extract of mangosteen rind of 1%, and distilled water of 45%. The evaluation results of the physical and chemical properties of the gel optimum formula revealed the viscosity of 2,345 cps, dispersive power of 6.59 cm, and pH of 6.74. Alpha-mangostin release test on the optimum formula revealed a flux value of 41.327 ?g/cm2/t1/2. From these results, it is concluded that the optimum formula has met the physical and chemical characteristics of a good gel.